A Study of Trends in B2C Online Buying in India - Joshi, Deepal; Achuthan, Sarla (Indian Journal of Marketing, 2016)
The e-commerce market in India is set to grow the fastest within the Asia-Pacific region between 2012 and 2016. Venture capitalists are pumping finance in the Indian e-commerce sector, corporate giants are entering this market, and 100% FDI is likely in this sector. Also, Internet penetration is increasing in India, coupled with the increasing base of social networking sites and sale of advanced smartphones and tablets. Apart from metros and large cities, even tier II and III cities and towns are registering considerable sales of products and services using the online channel. On the consumer side, several factors lead to staggering sales using online channels in India. Convenience, product variety, shopping comfort, enjoyment, ease of delivery, huge discounts, cash payment options, and increasing penetration of debit and credit cards are a few to name. However, using the Internet only as a medium to review and check products instead of buying, poor status of cyber laws in India, and challenge of reaching break-even point and making profits from that point continue to be the issues in this sector. In this light, in this study, we tried to identify trends in B2C online buying in the Indian context. This work would be of immense interest for academicians, researchers, and online retailers in India.